2016
DOI: 10.1097/md.0000000000004341
|View full text |Cite
|
Sign up to set email alerts
|

Macular microvasculature alterations in patients with primary open-angle glaucoma

Abstract: To evaluate and compare macular microvasculature changes in eyes with primary open-angle glaucoma (POAG) to normal eyes, and to assess associations among the retinal microvasculature, neural structural damage, and visual field loss.Ninety-nine eyes (68 patients with POAG and 31 normal subjects) were enrolled in this study. Thirty-five eyes with early-stage glaucoma (EG), 33 eyes with advanced-stage glaucoma (AG), and 31 normal eyes were included. An optical coherence tomography system with a split-spectrum amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
7
34
0
1
Order By: Relevance
“…This can explain why some studies that measured only the fovea or parafovea found no difference [32, 37]. The finding that the greatest differences between normal and glaucoma eyes were found in the inferotemporal sector further corroborates this theory [36, 47, 62, 70]. …”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…This can explain why some studies that measured only the fovea or parafovea found no difference [32, 37]. The finding that the greatest differences between normal and glaucoma eyes were found in the inferotemporal sector further corroborates this theory [36, 47, 62, 70]. …”
Section: Resultssupporting
confidence: 73%
“…A significant correlation was found between the OCTA parameters and visual field MD, between OCTA parameters and glaucoma stage, and, as previously described, between the OCTA and OCT parameters in the peripapillary area [6, 17-20, 22-24, 26, 28-30, 33, 35, 36, 38, 39, 41, 45, 48, 50, 71-75], the optic disc [19, 23, 29, 36, 51-53, 57, 58], and the macular area [21, 36, 38, 61, 62, 64, 69, 75, 76]. As mentioned above, the results for the parafoveal area were not significant in some of the studies [38, 70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, macula vessel densities did not differ between the control and the early glaucoma group (mean MD = -2.42). Another study [22] found a higher decrease of the superficial vessel density in the macula in both early and advanced glaucoma (8 and 20%). An explanation of this discrepancy could lie in the small macular scan area considered in our and Rao studies (3 × 3 mm) compared to the 6 × 6 mm in the study of Xu et al [22].…”
Section: Macular Vdmentioning
confidence: 99%
“…[4][5][6][7][8][9] Further, even though the macular involvement in glaucoma has been demonstrated, few papers have focused on the macular microvasculature in patients affected by this disease. [10][11][12][13][14][15] The purposes of the present study were (1) to evaluate both macular and peripapillary vessel perfusion density (VD) in glaucoma suspects (GS) and glaucoma (G) patients, (2) to correlate macular RGC and RNFL defects with macular and peripapillary VD, and (3) to evaluate the diagnostic accuracy of RGC and RNFL thicknesses and vascular parameters in detecting glaucoma.…”
mentioning
confidence: 99%